FAKTOR KARAKTERISTIK DIGITAL BRANDING DALAM KEBERHASILAN USAHA PADA PELAKU UMKM DESA GELAM JAYA - Sonny Santosa; Tri Angreni; Rini Novianti; Elizabeth Elizabeth; Andre Gustriandi (eCo-Buss, 2021)
Interesting issues related to branding always begun by a basic question ‘What is the biggest problem of a new online shop or start up, and how do we overcome it?’ If we observe people whose business focus in product selling, they mostly promote their product by explaining the excellence of their products to the customers, for example the soft material of clothes, the great taste of the food, the comfortable shoes, or efficacious and nutritious medicines. But, if we look closely, whether they convince the customers or not that the products they offer are the best, the tastiest, or the efficacious, the most comfortable, and the best selling in the market, thus we just see all of them as the common part. And there is actually a unique part greatly contributing to them, which is branding. Based on its aims, this research was conducted by using the method of descriptive verification, which is a method aimed at outlining problems related to the questions toward the independent variable. Thus, it is going to support the theories or previous researches related to branding. Data verification was compiled based on report of research used to assess the veracity of theoretical facts in the field, and later it was analyzed to test the research hypothesis conducted. The findings showed that value unit of search engine optimization (SEO) was dominant enough, 0.823, video marketing was 0.769, e-commerce platform was 0.734, user generated conted was 0.718, geofening technology was 0.569, micro influencer was 0.545, and social media marketing was 0.529.